Effect of Taxation on Domestic Investment in Nigeria - Nkem, Uchime, Helen; Sunday, Anichebe Alphonsus (International Journal of Economics, Business and Management Studies, 2019)
This study examined the effect of taxation on Domestic Investment in Nigeria; using time series data from 1995 to 2017. Data for the study was sourced from the Central Bank of Nigeria Statistical Bulletin and National Bureau of Statistics. The estimation technique adopted in the study was the Ordinary Least Square (OLS) Technique. The results of the estimates showed that: Taxation has long run relationship with Domestic investment in Nigeria; Personal income tax and Gross domestic product have non significant negative effects on Domestic investment in the long run, while company income tax has a significant positive effect on Domestic Investment. Value added tax has a non significant positive relationship with Domestic investment in the long run. In conclusion, the study finds a mixed result. Based on findings of the study, the following recommendation was made; Government should use money derived from taxation in providing adequate infrastructures like good roads, water and electricity. This will lower the cost of doing business in Nigeria.